Peningkatan Kedisiplinan dan Hasil Belajar Pendidikan Pancasila Menggunakan Model PjBL Siswa Kelas 1 SD Kanisius Sorowajan - Andromeda, Bravura; Brataningrum, Natalina Premastuti; Rustamti, Maria Indarti (Paedagogie, 2024)
The low attitude of discipline and learning outcomes of Pancasila Education, especially the material of Aku Suka Bergotong Royong in class 1A students of SD Kanisius Sorowajan in the 2022/2023 school year is the background of this research. In the initial observation activities on the disciplinary attitude of the students, the average score was 65 with a percentage of 60% and the student learning outcomes showed an average score of 60 with a percentage of students who reached KKTP of 40%. The purpose of this study is to 1) describe efforts to improve the attitude of discipline and learning outcomes of Pancasila Education of class 1A Kanisius Sorowajan Elementary School students by using the Project Based Learning model, 2) improve the learning outcomes of Pancasila Education of class 1A Kanisius Sorowajan Elementary School students by using the Project Based Learning model. This research uses the method of Classroom Action Research (PTK) model of Kemmis and Mc Taggart with four stages of research including planning, implementation, observation, and reflection. The research subjects were class 1A as many as 20 students consisting of 9 male students and 11 female students. Data collection techniques were obtained from the results of questionnaires and tests. The results of the disciplinary attitude questionnaire showed an increase in cycle 1 to 75 with a percentage of achievement of 75% and cycle 2 increased to 85 with a percentage of achievement of 85%. The test results showed an increase in learning outcomes in cycle 1 to 67.5 with a percentage achievement of 60% and in cycle 2 increased to 80 with a percentage achievement of 95%. This shows that Pancasila Education learning activities with the Project Based Learning learning model can improve students' discipline attitude and learning outcomes.